2019
DOI: 10.2105/ajph.2018.304895
|View full text |Cite
|
Sign up to set email alerts
|

From Disaster Response to Community Recovery: Nongovernmental Entities, Government, and Public Health

Abstract: In this article, we examine the role of nongovernmental entities (NGEs; nonprofits, religious groups, and businesses) in disaster response and recovery. Although media reports and the existing scholarly literature focus heavily on the role of governments, NGEs provide critical services related to public safety and public health after disasters. NGEs are crucial because of their ability to quickly provide services, their flexibility, and their unique capacity to reach marginalized populations. To examine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…Community-based organisations are increasingly recognised as critical partners in local disaster management (Chandra et al , 2013; Ritchie et al ., 2010; Drennan and Morrissey, 2019; Shih et al ., 2018; Sledge and Thomas, 2019). However, there has been little research examining the role of community-based organisations that support older adults ageing-in-place in building disaster resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based organisations are increasingly recognised as critical partners in local disaster management (Chandra et al , 2013; Ritchie et al ., 2010; Drennan and Morrissey, 2019; Shih et al ., 2018; Sledge and Thomas, 2019). However, there has been little research examining the role of community-based organisations that support older adults ageing-in-place in building disaster resilience.…”
Section: Introductionmentioning
confidence: 99%
“…During public health crises, as during the response to disasters, information, expertise, and formal and informal capacities to respond are distributed across jurisdictions and communication networks (Keller et al, 2012; Kenis et al, 2019). Importantly, nonstate actors play a critical role in supplementing the capacity of governments to provide needed services (Maher et al, 2020; Sledge & Thomas, 2019; Walsh et al, 2015). Nonprofit organizations, such as the American Red Cross, food banks, businesses, and religious groups, provide basic social services for those impacted and are formally included in the Federal Emergency Response Agency (FEMA)'s National Response Framework (Egan & Tischler, 2012; Gerber & Robinson, 2007; US Department of Homeland Security, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Public Health Emergency Preparedness and Response Capabilities developed by the United States Centers for Disease Control and Prevention (CDC) encourage public health agencies to partner with other organizations and community stakeholders during all stages of recovery [3]. Robust partnerships and a collaborative approach to disaster recovery can enhance and facilitate key recovery actions, including sharing resources and information, conducting ongoing needs assessments, and referring community members to services [11][12][13]. Studies based on real-world disaster recovery processes have also underscored the importance of partnerships and community engagement during disaster recovery; one case study found that undertaking a community-based participatory approach to providing public health services during disaster recovery facilitated the ability of the health sector to: identify, monitor, and address health needs and impacts in the community; connect community members to resources to support recovery; and contribute to the evidence base on health impacts of disasters [14].…”
Section: Introductionmentioning
confidence: 99%